Mn-substituted cerium oxide nanostructures and their magnetic properties. (August 2018) - Alla, S.K.; Kollu, P.; Meena, Sher Singh; Poswal, H.K.; Mandal, R.K.; Prasad, N.K.
Graphical abstract: Highlights: Mnx Ce1-x O2 (0.1 ≤ x ≤ 0.5) nanostructures were prepared by one step microwave refluxing method. The saturation magnetization values for the samples rose with increased Mn content. The oxygen vacancies inherently played crucial role in increasing the magnetization values. Abstract: In this study, we report the magnetic properties of nanostructured Mnx Ce1-x O2 (0 0.1 ≤ x ≤ 0.5) materials, synthesized via microwave refluxing technique. Phase purity of the samples was investigated using the structural characterization techniques such as X-ray diffraction (XRD) and transmission electron microscopy (TEM). These analyses indicated the substitution of Ce-ions with Mn-ions in the lattice. The progressive increase in the oxygen vacancies with increased dopant concentration was demonstrated by Raman, UV–vis and photoluminescence spectroscopic studies. X-ray photoelectron spectroscopy analysis further supported the presence of Mn 2+, Ce 3+ and Ce 4+ ions as well as oxygen vacancies in the samples. The Mn substituted CeO2 nanostructures were found to exhibit room temperature ferromagnetism (RTFM). There was a continuous improvement in the saturation magnetization ( M S ) values with increased Mn concentration. This might be due to the prevalence of surface oxygen vacancies and the systematic rise in their concentration with increased dopant content.